2022
DOI: 10.1029/2021jd036398
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Convective Mergers on the Evolution of Microphysical and Electrical Activity in a Severe Squall Line Simulated by WRF Coupled With Explicit Electrification Scheme

Abstract: Severe convective thunderstorms, which occur frequently during the warm season, cause significant loss of life and property amounting to several billion RMB in China. Among the threats they carry, lightning activity can be lethal and destructive. Convective merger (CM) is a process in which two or more convective cells or storms merge into a larger storm, then share a common cloud material and dynamical circulation, which is critical for the development, maintenance, and reinforcement of some intense weather s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…To investigate whether increasing the CCN concentration changes convection, Figure 2 shows the spatial distribution of radar reflectivity during different stages of the storm for different aerosol scenarios. Based on the characteristics of reflectivity and lightning activity (van den Broeke et al., 2008; Liu et al., 2021; Lu et al., 2022; C. Zhao et al., 2022), the different stages of storm development, that is, initial (Figures 2a, 2d, and 2g), developing (Figures 2b, 2e, and 2h), and pre‐mature (Figures 2c, 2f, and 2i), were identified. Convection developed later in the polluted run than in the Ctrl and clean cases.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether increasing the CCN concentration changes convection, Figure 2 shows the spatial distribution of radar reflectivity during different stages of the storm for different aerosol scenarios. Based on the characteristics of reflectivity and lightning activity (van den Broeke et al., 2008; Liu et al., 2021; Lu et al., 2022; C. Zhao et al., 2022), the different stages of storm development, that is, initial (Figures 2a, 2d, and 2g), developing (Figures 2b, 2e, and 2h), and pre‐mature (Figures 2c, 2f, and 2i), were identified. Convection developed later in the polluted run than in the Ctrl and clean cases.…”
Section: Resultsmentioning
confidence: 99%
“…Some observations have suggested that augmentation of total ice contents and robust mixed‐phase processes under polluted conditions eventually lead to higher lightning flash rates (Liu et al., 2021; Zhao et al., 2020). Meanwhile, larger CAPE and mid‐level RH also help to intensify lightning activity (Liu et al., 2011; Lu et al., 2022; Wang et al., 2018). The tangled influences of aerosol forcing and dynamics‐thermodynamic effects on electrification are still poorly understood based on convection‐resolved model simulation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The strong updraft via the horizontal transport of ice-phase particles may increases the collision rate and enhance the electri cation. The cloud bridge between two merging cell is one of lightning surged region (Lu et al, 2022). In Figures A (a , and 3b.…”
Section: Observed Tles During the Cell Merging And The Dissipation Of...mentioning
confidence: 99%
“…Cell merging is one of important processes to intensify the convective system (Westcott, 1994). Lu et al (Lu et al, 2022) investigate the cell merging and corresponding lightning activity using observation and simulation. Their results support that cell merging can enhance the lightning activity.…”
Section: Observed Tles During the Cell Merging And The Dissipation Of...mentioning
confidence: 99%